Public councils in Kazakhstan: a case of emergent participative democracy? - Knox, Colin; Janenova, Saltanat (Central Asian Survey, 2018)
As Kazakhstan aims to become one of the top 30 developed countries by 2050, it is increasingly turning to ways which will improve its governance, one of which is greater participation by its citizens in the decision-making processes of state agencies. A new initiative aimed at doing just that, the establishment of public councils, received legal backing in January 2016. The aim of public councils is to ‘strengthen democracy and the quality and responsiveness of public polices’ through the ‘public expression of matters of concern to Kazakh citizens’. This article offers a formative evaluation of the role performed by public councils and questions the extent to which they have achieved this aim. It draws on primary data from public officials, non-governmental organizations, ministries, and non-participant observation of public councils in Kazakhstan. It finds limited evidence of their effectiveness to date...
Keywords: Public councils in Kazakhstan